Better safe than sorry: Simplistic fear-relevant stimuli capture attention - Forbes, S.; Purkis, H.; Lipp, Ottmar (2011)
It has been consistently demonstrated that fear-relevant images capture attention preferentially over fear-irrelevant images. Current theory suggests that this faster processing could be mediated by an evolved module that allows certain stimulus features to attract attention automatically, prior to the detailed processing of the image. The present research investigated whether simplified images of fear-relevant stimuli would produce interference with target detection in a visual search task. In Experiment 1, silhouettes and degraded silhouettes of fear-relevant animals produced more interference than did the fear-irrelevant images. Experiment 2, compared the effects of fear-relevant and fear-irrelevant distracters and confirmed that the interference produced by fear-relevant distracters was not an effect of novelty. Experiment 3 suggested that fear-relevant stimuli produced interference regardless of whether participants were instructed as to the content of the images. The three experiments indicate that even very simplistic images of fear-relevant animals can divert attention. © 2010 Psychology Press.